2019
DOI: 10.1097/ccm.0000000000004016
|View full text |Cite
|
Sign up to set email alerts
|

Early Palliative Care Consultation in the Medical ICU: A Cluster Randomized Crossover Trial

Abstract: Objectives: To assess the impact of early triggered palliative care consultation on the outcomes of high-risk ICU patients. Design: Single-center cluster randomized crossover trial. Setting: Two medical ICUs at Barnes Jewish Hospital. Patients: Patients (n = 199) admitted to the medical ICUs from August 2017 to May 2018 with a positive palliative care screen indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
128
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(146 citation statements)
references
References 47 publications
2
128
1
4
Order By: Relevance
“…To understand the impact at a more granular level, consider the results of Ma et al's randomized, controlled trial of formal specialist consultations, which showed a substantial increase in code status changes and in transfers to hospice, along with reductions in ventilator days, number of tracheostomies performed, and rates of postdischarge emergency department visits or readmissions. 16 Taken together, these study results suggest that palliative consultations uncover patient-or surrogate-driven desires to limit aggressive therapies-desires that otherwise may go unrealized. Indeed, it is largely through this improved communication regarding expectations, prognosis, preferences, and resources that palliative medicine programs have been able to reliably boost levels of patient and family satisfaction.…”
Section: F R O N T I E R S O F C a R Ementioning
confidence: 69%
“…To understand the impact at a more granular level, consider the results of Ma et al's randomized, controlled trial of formal specialist consultations, which showed a substantial increase in code status changes and in transfers to hospice, along with reductions in ventilator days, number of tracheostomies performed, and rates of postdischarge emergency department visits or readmissions. 16 Taken together, these study results suggest that palliative consultations uncover patient-or surrogate-driven desires to limit aggressive therapies-desires that otherwise may go unrealized. Indeed, it is largely through this improved communication regarding expectations, prognosis, preferences, and resources that palliative medicine programs have been able to reliably boost levels of patient and family satisfaction.…”
Section: F R O N T I E R S O F C a R Ementioning
confidence: 69%
“…In the original trial, 242 patients were enrolled, but only 199 were eligible for the primary outcome. 6 Of these patients, only 132 survived to hospital discharge and had not been on suppressive antimicrobials or active treatment for a previous infection at the time of hospital admission. Of 132 patients, 36 patients (27.3%) changed their code status to do not resuscitate/do not intubate.…”
Section: Resultsmentioning
confidence: 99%
“…The details of the trial have recently been described. 6 Briefly, the trial was a single-center cluster randomized crossover trial (August 2017-May 2018) at Barnes-Jewish Hospital (1,250 beds). The study included a 6-week washout period halfway through the study, followed by crossing over to intervention or usual care of the 2 medical ICUs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations